Flexible leadership in the manufacturing sector. Issue 1 (19th December 2019) - Alat, Priya; Suar, Damodar
Abstract : Purpose: The purpose of this paper is to explore leader flexibility in the manufacturing sector. The objectives are to understand the nature of uncertainties that leaders face and how their personal attributes facilitate them in responding to uncertain situations. Design/methodology/approach: A total of 20 middle- and senior-level executives were interviewed, using seven semi-structured questions, from four states in India. Responses were analyzed using thematic analysis. Findings: In this paper, two themes were identified: the need for flexibility and competencies. The need for flexibility included the factors that warrant adaptability and the performance requirements, such as changes in external environment, reconciling opposing demands, unpredictability of human resources and day-to-day contingencies. Performance requirements included monitoring the environment, anticipating changes, creating shared meanings, developing adaptability in human resources, understanding contradictions and generating alternate solutions. Competencies included balancing different values, roles, and behaviors, coaching and team building skills, planning skills, systems thinking, social skills, conflict management skills and openness to learning. Research limitations/implications: Interviews were conducted with only executives; interviewing their subordinates may have revealed different perspectives. With the accounts being retrospective, few details may have been missed or exaggerated. Practical implications: The findings can be used to apprise leaders of the challenges they may face and develop competencies required for leader flexibility. Originality/value: Leadership research in the manufacturing sector is mostly focused on leaders' responses to environmental uncertainties. This research identifies the task demands associated with unpredictability of human factors and daily contingencies, and the competencies used to respond.